2019
DOI: 10.3390/ijms20225736
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of DNA-Protein Complex Formation upon Radiation-Induced DNA Damage

Abstract: The importance of determining at the cellular level the formation of DNA–protein complexes after radiation-induced lesions to DNA is outlined by the evidence that such interactions represent one of the first steps of the cellular response to DNA damage. These complexes are formed through recruitment at the sites of the lesion, of proteins deputed to signal the presence of DNA damage, and of DNA repair factors necessary to remove it. Investigating the formation of such complexes has provided, and will probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Similar protocols for selective depletion of unrelated protein molecules using a mild treatment with DNase or RNase have been used to improve the detection of the XPG, DDB2, XPC ( Dutto et al, 2017 ), and Ku80 ( Britton et al, 2013 ) at the lesion sites. Along with this, the live-cell imaging revealed that NER is highly dynamic process with a continuous exchange of the repair factors during the repair reaction ( Vermeulen, 2011 ; Ticli and Prosperi, 2019 ).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Similar protocols for selective depletion of unrelated protein molecules using a mild treatment with DNase or RNase have been used to improve the detection of the XPG, DDB2, XPC ( Dutto et al, 2017 ), and Ku80 ( Britton et al, 2013 ) at the lesion sites. Along with this, the live-cell imaging revealed that NER is highly dynamic process with a continuous exchange of the repair factors during the repair reaction ( Vermeulen, 2011 ; Ticli and Prosperi, 2019 ).…”
Section: Introductionmentioning
confidence: 86%
“…The progress in understanding mammalian NER was relatively slower than other DNA repair pathways, largely because of a conceptual and some technical hurdles. In the early stage, the specific biochemical reactions carried out by a majority of the mammalian NER proteins were identified using the in vitro DNA repair assays with purified proteins and from their equivalent proteins in bacteria and yeast ( Aboussekhra et al, 1995 ; Sugasawa et al, 1998 ; Ticli and Prosperi, 2019 ). However, these techniques lack the spatio-temporal properties ( Ticli and Prosperi, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations